The Extinction of Administrative Disciplinary Responsibility in Merger Cases, applied to Public Procurement - Baca Oneto, Víctor Sebastian (2015)
In this article, the extinction of disciplinary responsibility in cases where a companydisappears will be analyzed. To do this, firstly we will study cases of transmission of the responsability in the cases referred to the extinction of the legal personality . Finally, the Peruvian legislation on public procurement and the transfer of responsibilities in cases of extinction by merger of legal entities will be analyzed.